Feasibility of inspiratory muscle training to improve pulmonary and respiratory muscle function, and for attenuating sleep apnea symptoms in children and adolescent with obstructive sleep apnea and obesity: Case report - Sornkla, Siramon; Sonsuwan, Nuntigar; Pratanaphon, Sainatee (Journal of Associated Medical Sciences, 2022)
Background: Studies have demonstrated a potential risk of pulmonary and respiratory muscle dysfunction in individuals with obstructive sleep apnea (OSA) and/or obesity. Inspiratory muscle training (IMT) is an adjunct intervention designed to improve respiratory muscle strength, decrease severity of OSA, and to enhance sleep quality in adults with OSA. However, its effects on children with OSA and obesity are still largely unknown. Objectives: This case report aims to show the feasibility and the effects of IMT on pulmonary and respiratory muscle function and sleep apnea symptoms of children and adolescents with OSA and obesity. Case description: Four children and one adolescent who were diagnosed with OSA and classified as obesity underwent IMT with training load at 60% of the individual’s maximal inspiratory pressure (MIP) for 12 weeks. Results: No adverse effects occurred during evaluation and IMT. The participants’ compliance with IMT varied from 77.4% to 100%. After 12-week of IMT, MIP and maximal voluntary ventilation (MVV) increased from baseline, varying from 8.0% to 83.5% and 0.1% to 36.1%, respectively. Scores in the Sleep Related Breathing Disorder-Pediatric Sleep Questionnaire (SRBD-PSQ) tended to decrease rapidly at week 3. Thereafter, participants responded differently toward the end of IMT. Changes in pulmonary function variables were not observed. Conclusion: Improvements in respiratory muscle strength, endurance, and SRBD-PSQ scores occurred after IMT, suggesting the feasibility of IMT for increasing inspiratory muscle performance and for ameliorating sleep apnea symptoms in children and adolescents with OSA and obesity. However, pulmonary function was unaffected by IMT.